Drought and Oxidative Stress in Flax (Linum usitatissimum L.) Entails Harnessing Non-Canonical Reference Gene for Precise Quantification of qRT-PCR Gene Expression - Prasanta K. Dash; Rhitu Rai; Sharat Kumar Pradhan; Sheelavanta Matha Shivaraj; Rupesh Deshmukh; Rohini Sreevathsa; Nagendra K. Singh (MDPI AG, 2023)
Flax (Linum usitatissimum L.) is a self-pollinating, annual, diploid crop grown for multi-utility purposes for its quality oil, shining bast fiber, and industrial solvent. Being a cool (Rabi) season crop, it is affected by unprecedented climatic changes such as high temperature, drought, and associated oxidative stress that, globally, impede its growth, production, and productivity. To precisely assess the imperative changes that are inflicted by drought and associated oxidative stress, gene expression profiling of predominant drought-responsive genes (AREB, DREB/CBF, and ARR) was carried out by qRT-PCR. Nevertheless, for normalization/quantification of data obtained from qRT-PCR results, a stable reference gene is mandatory. Here, we evaluated a panel of four reference genes (Actin, EF1a, ETIF5A, and UBQ) and assessed their suitability as stable reference genes for the normalization of gene expression data obtained during drought-induced oxidative stress in flax. Taking together, from the canonical expression of the proposed reference genes in three different genotypes, we report that EF1a as a stand-alone and EF1a and ETIF5A in tandem are suitable reference genes to be used for the real-time visualization of cellular impact of drought and oxidative stress on flax.